THE ROLE OF GRAMMAR GAMES IN TEACHING ENGLISH - Nazarov, Rustam (Журнал иностранных языков и лингвистики, 2023)
This article is about role of grammar games in teaching English. The game in the process of training contributes to the solution of quite specific tasks: it creates a psychological mood for verbal communication, prepares for the development of situational spontaneous speech and helps in choosing the optimal speech option.